2013
DOI: 10.2174/18715273113129990072
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Oxidative Stress and Mitochondrial Failure in the Pathobiology of Alzheimer’s Disease: A New Approach to Therapy

Abstract: Vascular and metabolic dysfunctions and mitochondrial failure are now believed to be contributors to Alzheimer's disease (AD) pathogenesis. Vascular dysfunction includes reduced cerebral blood flow (CBF), blood-brain barrier (BBB) disturbances and cerebral amyloid angiopathy (CAA). Mitochondrial failure results in deregulation of Ca(2+) homeostasis and elevated reactive oxygen species (ROS) generation, both of which are linked to neurotoxicity. Increased levels of ROS stimulate proinflammatory gene transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 0 publications
2
50
0
Order By: Relevance
“…In addition to activating cell death, previous studies have demonstrated that caspase-3 also has fundamental roles in signal transduction (10,11 of the normal cellular metabolism of oxygen; however, a dramatic increase in ROS levels may lead to oxidative stress. It has been demonstrated that ROS induced by ionizing radiation are capable of triggering oxidative cellular damage and stimulating the activation of intracellular signaling pathways (12). The brain, which is a major metabolizer of oxygen with relatively poor protective antioxidant mechanisms, is particularly vulnerable to the ROS.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to activating cell death, previous studies have demonstrated that caspase-3 also has fundamental roles in signal transduction (10,11 of the normal cellular metabolism of oxygen; however, a dramatic increase in ROS levels may lead to oxidative stress. It has been demonstrated that ROS induced by ionizing radiation are capable of triggering oxidative cellular damage and stimulating the activation of intracellular signaling pathways (12). The brain, which is a major metabolizer of oxygen with relatively poor protective antioxidant mechanisms, is particularly vulnerable to the ROS.…”
Section: Introductionmentioning
confidence: 99%
“…ROS produced at the early phase of neuronal apoptosis act as mediators of intracellular apoptotic signaling cascades (5), and pathologically accelerate the release of cytochrome c from mitochondria (6,7). ROS production evidently increases following ischemia, which leads to oxidative stress (8)(9)(10). Studies have revealed that at least some of the effects on cells of exposure to ROS are similar to those of ischemic insult.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, microglia become activated either by a direct interaction with misfolded Aβ molecules via pattern recognition receptors (PRR), or by complement activation in the response to Aβ depositions which leads to the formation of the pro-inflammatory molecule C5a [14]. Enhanced microglia activation then leads to excessive release of proinflammatory cytokines [20], chemokines [21,22], and further complement components [23,24], as well as the release of reactive oxygen and nitrogen species [25,26]. These pro-inflammatory mediators cause a number of stress conditions which, in turn, are supposed to reinforce Aβ production and aggregation [28,30,31,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Aβ aggregates cause direct cytotoxicity and self-propagation, but also a constant, selfsustaining inflammatory environment by prolonged activation of astroglial [17,18] and microglial cells [19]. Activation of microglia by Aβ and complement is supposed to promote the excessive release of proinflammatory cytokines [20], chemokines [21,22], and further complement components [23,24], as well as the release of reactive oxygen and nitrogen species [25,26], altogether leading to dysfunction and loss of synapse signaling [27]. Pro-inflammatory mediators provoke a number of stress conditions which, in turn, can enhance APP production and processing to amyloid peptides (Aβ 1-42) [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%